every equations that the form ax^2+bx+c=0 deserve to be addressed using the quadratic formula: frac-b±sqrtb^2-4ac2a. The quadratic formula provides two solutions, one once ± is enhancement and one when it is subtraction.

You are watching: What are the solutions of the equation x^2+4x+4=25


This equation is in standard form: ax^2+bx+c=0. Instead of 1 for a, -4 for b, and also -39 because that c in the quadratic formula, frac-b±sqrtb^2-4ac2a.
*

The two services aredisplaystylex=pm2sqrt2+1 .Explanation:First, division the whole equation by two: displaystyle2x^2-4x-14=0displaystylex^2-2x-7=0 ...
x2-4x-4=25 Two remedies were discovered : x =(4-√132)/2=2-√ 33 = -3.745 x =(4+√132)/2=2+√ 33 = 7.745 Rearrange: Rearrange the equation by subtracting what is to the right of the equal authorize from ...
2x2-7x-15=0 Two solutions were found : x = -3/2 = -1.500 x = 5 action by action solution : action 1 :Equation in ~ the finish of step 1 : (2x2 - 7x) - 15 = 0 step 2 :Trying to element by separating ...
x2-14x-14=0 Two options were found : x =(14-√252)/2=7-3√ 7 = -0.937 x =(14+√252)/2=7+3√ 7 = 14.937 action by action solution : step 1 :Trying to variable by splitting the center term ...
x2-4x-14=0 Two services were found : x =(4-√72)/2=2-3√ 2 = -2.243 x =(4+√72)/2=2+3√ 2 = 6.243 action by step solution : step 1 :Trying to aspect by separating the center term ...
x2-4x-148=0 Two solutions were discovered : x =(4-√608)/2=2-2√ 38 = -10.329 x =(4+√608)/2=2+2√ 38 = 14.329 action by step solution : step 1 :Trying to element by separating the middle term ...
More Items
*
*

*
*
*

All equations that the kind ax^2+bx+c=0 have the right to be solved using the quadratic formula: frac-b±sqrtb^2-4ac2a. The quadratic formula gives two solutions, one as soon as ± is addition and one when it is subtraction.
This equation is in standard form: ax^2+bx+c=0. Substitute 1 for a, -4 because that b, and -39 for c in the quadratic formula, frac-b±sqrtb^2-4ac2a.
Quadratic equations such as this one have the right to be solved by perfect the square. In order to finish the square, the equation must an initial be in the form x^2+bx=c.
Divide -4, the coefficient the the x term, through 2 to gain -2. Then add the square that -2 come both sides of the equation. This step makes the left hand next of the equation a perfect square.

See more: How Many Cups Are In 240 Fl Oz To C? How Many Cups Is In 240 Oz


Factor x^2-4x+4. In general, as soon as x^2+bx+c is a perfect square, that can always be factored together left(x+fracb2 ight)^2.
left< eginarray together l 2 & 3 \ 5 & 4 endarray ight> left< eginarray l l l 2 & 0 & 3 \ -1 & 1 & 5 endarray ight>
*
*

*
*

EnglishDeutschEspañolFrançaisItalianoPortuguêsРусский简体中文繁體中文Bahasa MelayuBahasa Indonesiaالعربية日本語TürkçePolskiעבריתČeštinaNederlandsMagyar Nyelv한국어SlovenčinaไทยελληνικάRomânăTiếng Việtहिन्दीঅসমীয়াবাংলাગુજરાતીಕನ್ನಡकोंकणीമലയാളംमराठीଓଡ଼ିଆਪੰਜਾਬੀதமிழ்తెలుగు